2017
DOI: 10.1177/0363546517739625
|View full text |Cite
|
Sign up to set email alerts
|

Do Outcomes of Osteochondral Allograft Transplantation Differ Based on Age and Sex? A Comparative Matched Group Analysis

Abstract: This study provides evidence that OCA is a safe and reliable treatment option for osteochondral defects in patients aged ≥40 years. Male and female patients had similar outcomes. Patients aged <40 years demonstrated lower KOOS symptom subscores postoperatively compared with older patients, potentially attributable to higher expectations of return to function postoperatively as compared with older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 26 publications
9
67
0
Order By: Relevance
“…With a longer follow-up and more experience in cartilage restoration for older patients with focal cartilage lesions and without osteoarthritis, we hope to eventually further define the role of biological restoration as a method for long-term joint preservation or a bridge to total joint replacement based on the clinical situation. When added to recent studies conducted by Frank et al 8 and Wang et al, 15 our longitudinal regression modeling results and clinical outcomes support the position that OCA transplantation is a reasonable treatment modality for older patients based on age alone.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…With a longer follow-up and more experience in cartilage restoration for older patients with focal cartilage lesions and without osteoarthritis, we hope to eventually further define the role of biological restoration as a method for long-term joint preservation or a bridge to total joint replacement based on the clinical situation. When added to recent studies conducted by Frank et al 8 and Wang et al, 15 our longitudinal regression modeling results and clinical outcomes support the position that OCA transplantation is a reasonable treatment modality for older patients based on age alone.…”
Section: Resultssupporting
confidence: 75%
“…A third limitation is the lack of demographic factors, including smoking and workers’ compensation status, which may be age-dependent confounding variables. Frank et al 8 reported a significantly higher proportion of workers’ compensation claims but no difference in clinical outcomes in the older group relative to the younger group; however, they did not assess specifically for interactions between variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, patients were not stratified regarding sex or age, variables that were previously shown to affect OCA outcomes. 9,19,70…”
mentioning
confidence: 99%
“…20,26 Patients who have multifocal or bipolar reciprocal lesions often have additional injuries of the knee, such as meniscal tears or insufficiency, but are less than 50 years of age and lead active lifestyles. 10 Furthermore, there are limited published data regarding the clinical outcomes of patients treated with OCA with the dowel technique, that is, 2 overlapping allograft plugs for a single, elongated, or oblique lesion in the knee. 18…”
mentioning
confidence: 99%